Physiological jump in erythrocyte redox potential during Plasmodium falciparum development occurs independent of the sickle cell trait - Haag, Marvin; Kehrer, Jessica; Sanchez, Cecilia P.; Deponte, Marcel; Lanzer, Michael (Redox Biology, 2022)
The redox state of the host-parasite unit has been hypothesized to play a central role for the fitness of the intraerythrocytic blood stages of the human malaria parasite Plasmodium falciparum. In particular, hemoglobinopathies have been suggested to cause a more oxidizing environment, thereby protecting from severe malaria. Here we determined the redox potential of infected wild-type (hemoglobin AA) or sickle trait (hemoglobin AS) erythrocytes using parasite-encoded variants of the redox-sensitive green-fluorescent protein 2 (roGFP2). Our non-invasive roGFP2 single-cell measurements revealed a reducing steady-state redox potential of −304 ± 11 mV for the erythrocyte cytosol during ring-stage development and a rather sudden oxidation to −278 ± 12 mV during trophozoite-stage development around 28 h post invasion. There was no significant difference between wild-type or sickle trait erythrocytes regarding the stage dependence and the detected increase of the redox potential during the intraerythrocytic life cycle. The steady-state redox potential of the parasite cytosol, between −304 and −313 mV, was highly reducing throughout the life cycle. The redox potential in the parasitophorous vacuole at the interface between the secretory pathway and the erythrocyte was −284 ± 10 mV and remained stable during trophozoite-stage development with implications for the export of disulfide-containing proteins. In summary, P. falciparum blood stage development from the late ring to the early trophozoite stage causes a physiological jump in erythrocyte redox potential irrespective of the presence or absence of hemoglobin S.
Online verfügbar 10 November 2022, Artikelversion 16 November 2022
Gesehen am 25.01.2023